(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The paper includes rapid advancement in data mining, traditional data analysis methods are blended with sophisticated algorithms itself is data mining is seen. Data categorization, challenges, steps followed, techniques used are included here. K- Means, a clustering algorithm is efficient among other clustering algorithms includes its comparison with HAC and DBSACN algorithm techniques.